DNA barcoding of some species of the genus Capoeta Valenciennes, 1842 from Kurdistan Region, Iraq. - Gashaw F. Agha; Samir J. Bilal; Shamall M.A. Abdullah (Zanco Journal of Pure and Applied Sciences, 2023)
The genus Capoeta belongs to the Cyprinidae family and can be found in many of the inland waters of Middle Eastern nations. They are systematically complex species, many of which cannot be distinguished based on morphology. Genetic techniques like DNA barcoding may be used to identify species due to the limits of such species’ morphological identification, although their genetic links have not yet been fully elucidated. The current study provides information on the genetic structure of three Capoeta species (C. damascina, C. trutta, and C. umbla) found in the Greater Zab River/ Bekhme Dam of the Kurdistan Region- Iraq. In order to confirm the identification of Capoeta species at the molecular level, the mitochondrial cytochrome oxidase I (COI) gene was sequenced. The interspecific genetic between species was (0.003) to (0.064). The maximum likelihood phylogeny indicates a consensus tree topology containing two branches, the first branch is divided into two subbranches including C. damascina and C. umbla and the second branch includes C. trutta. The results suggest that COI gene sequencing can be used to identify Capoeta species from streams in the Kurdistan Region, which is one of the first steps to improving the genetic understanding of Capoeta species.